From analytical philosophy to philosophy of languaje and hermeneutics: the case of historiography (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
There are two historiographic prospects of analytical philosophy: Hempel’s neopositivism and Gardiner and Danto’s analytical philosophy of history. According to Hempel, the model of historiography should be the same as all scientific knowledge, namely, the nomothetic model of the physical and natural sciences. According to Gardiner and Danto, however, this model must arise from the purpose of historians and language consistent with those purposes. Gardiner and Danto’s conclusions opened the possibility of a new analyticalperspective, the historiographic text, prompting the debate toward the philosophy of language (White, 1992) and hermeneutics (Ricoeur, 2008).
Keywords: Historiography; Neo-positivism; Analytical philosophy of history; Linguistic turn; Hermeneutic philosophy